The Influence of Service Quality, Price Promotion and Brand Image on Customer Loyalty - Vincent Leonardo; Vanessa Klise; Windy Novita Sari; Devinna Chairman; Muhammad Agung Anggoro (Institute of Computer Science (IOCS), 2021)
This research is intended to examine and analyze the effect of service quality, price, promotion and brand image on customer loyalty at PT. Jaya Anugerah Sukses Abadi which is a company engaged in the supermarket with 5 star facilities. This study uses explanatory research methods. The number of customer populations is unknown so that the sampling technique in this study uses incidental sampling by using a sample of 150 respondents. The instrument used to conduct this research is a questionnaire which will first be tested for validity and reliability then will test the sample data which is quantified first using multiple regression. The findings of this study are partially service quality, promotion and brand image have a positive effect on customer loyalty while price has a negative effect on customer loyalty. Simultaneously the quality of service, price, promotion and brand image have a significant effect on customer loyalty with the amount of Adjusted R Square, which is 21.1%, the remaining 78.9% is influenced by other variables.